Spatial Mapping of On-road Traffic Emission for Air Quality Management: A Case of Vinh Phuc Province - Huong Quynh, Pham; Pham Nguyet Anh; Thai Kim Thanh; Chu Tuong Mai; Ho Quoc Bang (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2024)
Vinh Phuc province is in the northern key economic region of Vietnam. The province has been facing challenges in air quality management as the number of vehicles has rapidly increased to meet the rising demand for transportation resources. This research was aimed to conduct an emission inventory and to build a spatial emission map for traffic activities in an attempt to improve air quality management in Vinh Phuc province. The vehicles were categorized into 5 groups: motorcycles, cars, light-duty vehicles (LDVs), heavy-duty vehicles (HDVs) and buses. Meanwhile, the streets were also categorized into 5 groups: highways, rural roads, urban streets, suburban streets and industrial streets. The results showed that motorcycles were the main means of transportation (93% of total vehicles) and they were also the major contributors to total emissions of NOx, CO, VOCs (volatile organic compounds), CH4, NMVOCs (non-methane volatile organic compounds) and especially in the cases of CO, CH4, VOC and NMVOC emissions which contributed more than 90% of emissions. Cars were the main source of SO2 emissions, contributing 51% of total SO2 road traffic emissions. The emissions of TSP (total suspended particulate), PM10 and PM2.5 were mostly generated from buses (about 32%), followed by motorcycles (about 18%). LDVs and HDVs contributed 18% and 15% to total particulate matter emissions, respectively. Spatial distribution analysis of CO, NOx, SO2, TSP, NMVOC and PM2.5 which involved visual identification in polluted areas, showing that high emissions were in the southeast part of the province and the most polluted areas were Vinh Yen city, followed by Binh Xuyen district and Phuc Yen city. These results provide suggestions for local governments on how to design effective air quality control strategies.